Risks and complications of portal hypertension with Pregnancy - M.Ahmed, Khalid Yassin; M.Saeed, Amel Kamil; Taha, Mustafa Marwan; K.Y.M, Ayad (مجلة الجزيرة للعلوم الصحية; مجلد 11 عدد 1 (2015), 2015)
Portal hypertension is a common daily encountered health problem in endemic Schistomaiasis areas in Sudan. Females at child bearing age with portal hypertension and its complications are considered as a clinical challenge for general practitioners, obstetricians and gastroenterologists, especially when presenting during late trimesters  with unplanned pregnancy.  Portal hypertension with pregnancy per say is considered as risky combination, with a significantly high morbidity and mortality for both mother and fetus. Affected mother might develop hazardous bleeding (hematemesis, malena or postpartum hemorrhage), hepatic encephalopathy or even death in 2- 18% of cases. Additional complications can be faced due to associating anemia, enlarged spleen or liver and possible pancytopnea, which may affect the course of pregnancy and mode of delivery. Fetal loss is a recognized complication, ranges between 11- 18%. Fetal death usually happens as a consequence of preterm delivery, intrauterine growth restriction (IUGR) and/or intra uterine jeopardize  . Here is a reporting case of young lady who presented to an obstetric unit in her third trimester with an unbooked and unplanned  pregnancy, with history of repeated cesarean sections, post Schistomaiasis portal hypertension , pancytopnea, and intra uterine fetal death . High risk cesarean section was performed after optimizing her general condition, correcting of her anemia, coagulation profile and platelets, in spite of the ongoing effect of her hypersplenism which was further complicated by IUFD induced DIC.  In conclusion,.  An agreed protocol involving gastroenterologist and obstetrician is warranted for care of such a patient pre- conceptionally, antenatal, intra partum and post partum. Management of such a patient should only be done at tertiary care centers by a multidisciplinary team with good facilities for intensive care and blood transfusion.